Unsatisfactory glycemic control in type 2 Diabetes mellitus patients: predictive factors and negative clinical outcomes with the use of antidiabetic drugs - Maria Aparecida Marczynski; Karine Laura Cortellazzi; Sílvio Barberato-Filho; Rogério Heládio Lopes Motta; Alexandre Eduardo Franzin Vieira; Maria Teresa Verrone Quilici; Cristiane de Cássia Bergamaschi
ABSTRACT Many factors can interfere with glycemic control in patients with type 2 diabetes mellitus and this patient group has an increased risk of experiencing drug-related negative outcomes (DNO). The aim of this study was to identify the predictive factors of unsatisfactory glycemic control and DNO in this group of patients. A cross-sectional study was conducted collecting data from prescriptions and interviews with 100 patients of the Endocrinology Clinic of the Hospital Complex of Sorocaba, São Paulo, Brazil. Variables associated with unsatisfactory glycemic control were determined and the DNO associated with antidiabetic drugs identified. Age (<65 years) (OR=4.09), family history of diabetes (OR=3.24), use of combined therapy to treat diabetes (2-4 antidiabetic drugs) (OR=5.13) and presence of DNO (OR=5.92) were found to be predictive factors for poor patient glycemic control. DNO were observed in 49% of the patients and were caused predominantly by ineffectiveness in patients with poor glycemic control (p<0.05). There was no significant difference between groups (satisfactory and unsatisfactory glycemic control) for DNO caused by safety issues (p>0.05). Characterization of the profile of patients with uncontrolled diabetes and of aspects associated with drug treatment can contribute to the planning of interventions to improve patient care.